Pengaruh Kualitas Pelayanan Administrasi terhadap Kepuasan Peserta Didik di MTs Negeri 1 Model Palembang - Hasbi, M (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2018)
This research examines the influence of the administration service quality toward students’ satisfaction in Islamic Junior High School 1 Model Palembang. This research includes the total population of 283 students of grade VIII. Therefore, based on Slovin formula, there are 74 students involved as the research samples. The data is analysed using quantitative method namely doubled linear regression. Meanwhile, the testing stages include classical assumption (Multicolinearity, heteroskedatisidas, and normality testing). In classical assumption test, multicolinearity free regression model appears while heteroskedatisidas does not occur. It is mormally distributed. Therefore, based on the classical assumption, the doubled linear regression can be utilized in this research. The result shows that the regression is Y = 9.961 + (-0.065) X1+ 0.152 X2 + 0.074 X3+ 0.459 X4 + 0.000 X5, and Fcount = 4,283 sig 0,002 < 0,05. Therefore it can be understood that the quality of the administration service which includes physical evidence, assurance, emphaty, excellence, and responsiveness clearly influences students’ satisfaction in which the emphaty (X4) serves as the highest contributing factors with t count= 0,410 sig 0,00 < 0,05.